The Review Of The Concepts And Relationship Between Job Performance And Transformational Leaderships Style (Sains Humanika, 2015)
Since unit potency, cohesion, and performance are valuable concepts for the leaders to predict operational process of an organization in the future, so exploring knowledge in leadership styles are considered great challenge for scholars. Despite the subject of transformational leadership is studied more in the HR context, the relationship between transformation leadership and job performance is still unclear. Also, recently the concepts of leadership style and job performance are augmented as strong constructs in the literature. Hence, the scholars challenge to classify the concepts as well as the relationship between them. In this vein, the aim of this study is to make clear the intangible variables and measuring them in different studies and benchmarking their relationship. Although the existing more constructs which are influencing job performance; the researchers believe that transformational leadership has played the key role to enhance efficiency of job performance of individuals as managers and subordinates who are working in the organization.Â Â
Keywords: Job performance; transformational leadership; leadership styles; unit performance; transformational theory.